EXTRACTION OF CRUDE PALM OIL AND PALM KERNEL OIL USING THERMALLY ASSISTED MECHANICAL DEWATERING (TAMD) - HASSIN @ HASHIM, HASMIERA (2020)
Conventional palm oil extraction via screw press and various palm oil extraction pose major drawbacks such as low oil yield, energy intensive, high pressure operation and utilization of hazardous materials. In this study, thermally assisted mechanical dewatering was evaluated as a possible alternative to extract crude palm oil (CPO) and palm kernel oil (PKO) from mesocarp and palm kernel respectively. Response Surface Methodology (RSM) with central composite design (CCD) was conducted to obtain the optimum condition for the extraction of palm oil. At the optimum condition of 75.0 °C, 6.7 bar and 60 minutes of extraction time, CPO yield of 70.90 wt% was achieved compared to the conventional method, mechanical screw press with CPO yield of 61.0 wt%.